Assessment of the Risk Factors of Coronary Artery Diseases in Al-Nasiriyah City - Omar, led; Mansour, Khalida (Iraqi National Journal of Nursing Specialties, 2014)
Objective: to assess the risk factors of coronary artery disease patients.Methodology: A non-probability (purposive) sample of (100) patients. The study population consisted ofa sample of adults from both genders whose ages were 30 years and more, and was newly diagnosed ashaving CAD by coronary angiography in the cardiac catheterization unit of An Nasiriyah heart center.Results: The result of the study showed that the most common modifiable risk factors were low HDL-Clevels (58%), smoking (53%), hypertension (46%), diabetes mellitus (34%), obesity (30%), hightriglycerides (19%), hypercholesterolemia (17%), and high LDLC (14%). All these factors were positivelyand significantly associated with the development of CAD. Whereas, the most common non-modifiablerisk factors were age 50 years and more, sex, family history of CADRecommendation: Based on the above results, this study recommends conducting educational programstargeting patients and their families about coronary artery disease (severity and risk factors of disease,who the patient can control himself to avoid complications), this can be achieved through governmentorganization or non- government organization